Facile heterogeneously catalyzed nitrogen fixation by MXenes - Gouveia, José D. (2020)
The rate-limiting step for ammonia (NH3) production via the Haber–Bosch process is the dissociation of molecular nitrogen (N2), which requires quite harsh working conditions, even when using appropriate heterogeneous catalysts. Here, motivated by the demonstrated enhanced chemical activity of MXenes— a class of two-dimensional inorganic materials— toward the adsorption of quite stable molecules such as CO2 and H2O, we use density functional theory including dispersion, to investigate the suitability of such MXene materials to catalyze N2 dissociation. Results show that MXenes exothermically adsorb N2, with rather large adsorption energies ranging from −1.11 to −3.45 eV and elongation of the N2 bond length by ∼20%, greatly facilitating their dissociation with energy barriers below 1 eV, reaching 0.28 eV in the most favorable studied case of W2N. Microkinetic simulations indicate that the first hydrogenation of adsorbed atomic nitrogen is feasible at low pressures and moderate temperatures, and that the production of NH3 may occur above 800 K on most studied MXenes, in particular, in W2N. These results reinforce the promising capabilities of MXenes to dissociate nitrogen and suggest combining them co-catalytically with Ru nanoparticles to further improve the efficiency of ammonia synthesis.